Infinity Theory - Ahmed Mezher Marir (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
. This research defines Infinity, Inverse of Infinity, and Inverse of zero, the concept of approach, the symbol (a,b):y and show that, Infinity theory: i- Infinity is a natural number i.e (∞∈N). ii- The Inverse of infinity is not equal to zero and the Inverse of zero is not equal to infinity (1/∞≠0,1/0≠∞). Also, show that if 1/∞ is real number, then 1/∞ equals zero. And the set of real numbers is equals to the set of rational numbers (R=Q).